CONTEXTUALIZATION OF CULTURAL FIQH IN THE BALIMAU KASAI TRADITION: Integration Between Islamic Values and Kampar Local Culture - Asrizal; Armita, Pipin; Rizki, Muh. (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2019)
This study aims to examine the integration of Islamic values and local culture of Kampar that is wrapped up as cultural fiqh in the Balimau Kasai tradition. The tradition of Balimau Kasai is a tradition of welcoming the holy month of Ramadan by bathing with traditional ingredients and gathering at the river’s edge. The found four dimensions of integration of Islamic values and the local culture of Kampar in the Balimau Kasai tradition, namely: (1) the Balimau Kasai is held by the Kampar community as a form of gratitude of being able to meet with the month of Ramadan, (2) the Balimau Kasai is a form of joy and happiness with the coming of Ramadan, (3) the Balimau Kasai is a means of cleaning and purifying thebody and spiritually, (4) the Balimau Kasai is a place to establish harmonious relationship (silaturrahim), and (5) the Balimau Kasai is a moment to forgive each other. Based on these four dimensions, the Balimau Kasai tradition is not only a local cultural tradition, but also a form of inculcation of Islamic values.